2009
DOI: 10.1038/aps.2009.73
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of meloxicam following oral and transdermal administration in Beagle dogs

Abstract: Aim:The potential for topical delivery of meloxicam was investigated by examining its pharmacokinetic profiles in plasma and synovial fluid following oral and transdermal administration in Beagle dogs. Methods: The experiment was a two-period, crossover design using 6 Beagle dogs. Meloxicam tablets were administered orally at a dose of 0.31 mg/kg, and meloxicam gel was administered transdermally at a dose of 1.25 mg/kg. Drug concentrations in plasma and synovial fluid were determined by liquid chromatography-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…Meloxicam is a slightly preferential inhibitor of COX‐2 at therapeutic doses . Inhibition of COX‐2 prevents the production of certain inflammatory prostaglandins from the arachidonic acid pathway, which are induced by inflammatory stimuli in pathological conditions .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meloxicam is a slightly preferential inhibitor of COX‐2 at therapeutic doses . Inhibition of COX‐2 prevents the production of certain inflammatory prostaglandins from the arachidonic acid pathway, which are induced by inflammatory stimuli in pathological conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Meloxicam is a slightly preferential inhibitor of COX-2 at therapeutic doses. [3][4][5] Inhibition of COX-2 prevents the production of certain inflammatory prostaglandins from the arachidonic acid pathway, which are induced by inflammatory stimuli in pathological conditions. 31 COX-1 is referred to as a constitutive or "housekeeping" enzyme and occurs naturally in many tissues of the body at a fairly constant concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between these studies and studies demonstrating safety of transdermal NSAID delivery in animals (Yuan et al, 2009), the groundwork for clinical research involving the delivery of NSAIDs to treat peripheral nerve pain appears complete. The next logical step for this work is to take the results of these works, estimate dose transfer levels, and titrate the dose in the SonoBandage to ensure the greatest area of effective treatment concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic characteristics in plasma and synovial fluid were studied after administration of MX by the oral and transdermal route in beagle dogs. The higher drug level in synovial fluid than plasma suggested MX was directly delivered to the site of administration, which demonstrated that drug delivery of MX via skin had great potential to reduce the systemic adverse effects (Yuan et al, 2009). The pharmacokinetic profiles were evaluated by applying 0.5 g MX gel on rat skin, which reached the highest plasma concentration (C max ) of 48.48 ± 6.57 mg/ml at 2 h (T max ) (Gupta et al, 2002).…”
Section: Pharmacokinetics Studies Of MX Delivery Via Skinmentioning
confidence: 99%